Gut Microbiota Regulation and Their Implication in the Development of Neurodegenerative Disease - Peilin Sun (MDPI AG, 2021)
In recent years, human gut microbiota have become one of the most promising areas of microorganism research; meanwhile, the inter-relation between the gut microbiota and various human diseases is a primary focus. As is demonstrated by the accumulating evidence, the gastrointestinal tract and central nervous system interact through the gut–brain axis, which includes neuronal, immune-mediated and metabolite-mediated pathways. Additionally, recent progress from both preclinical and clinical studies indicated that gut microbiota play a pivotal role in gut–brain interactions, whereas the imbalance of the gut microbiota composition may be associated with the pathogenesis of neurological diseases (particularly neurodegenerative diseases), the underlying mechanism of which is insufficiently studied. This review aims to highlight the relationship between gut microbiota and neurodegenerative diseases, and to contribute to our understanding of the function of gut microbiota in neurodegeneration, as well as their relevant mechanisms. Furthermore, we also discuss the current application and future prospects of microbiota-associated therapy, including probiotics and fecal microbiota transplantation (FMT), potentially shedding new light on the research of neurodegeneration.